(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2024)
The demand for innovative eco-friendly ingredients is a current trend in the pharmaceutical and cosmetic fields. Starches can be a good alternative because their gelatinization property could increase the stability of emulsions. The objective of the present study was to develop a gel formulation based on tapioca and corn starch and to evaluate its stability, physical-mechanical and sensory properties according to the experimental design. A general full factorial experimental design with three levels was elaborated for each polysaccharide under study. The best formulation was evaluated in terms of rheological and sensorial properties. Only the formulation with tapioca and corn starch in combination was stable, showing a thixotropic behavior without changes in rheological parameters after 28 days. Sensorial analysis classified the formulation as soft, easy to spread and giving a hydration sensation. The nature of the polymers could be responsible for a synergistic effect on the spreadability parameter. According to the results obtained, the use of starches for the development of topical products can be suggested as a natural alternative to the polymers and silicones commonly used as rheological additives. The developed formulation could be a green alternative with proven physical-mechanical stability and excellent sensorial properties.